An Interactive Mobile Application for the Visually Impaired to Have Access to Listening Audio Books with Handy Books Portal - Meenakshi, Avanthika; Sundar, Shyam; Nancy, Silviya (International Journal of Interactive Mobile Technologies (iJIM), 2015)
Mobile phones are used in almost all aspects of life by people. But in the case of visually impaired, they are still a step behind in using smart phones for various purposes. Having interactive android OS, navigation and travel aiding apps using sensors and voice user interfaces (VUI) or the voice response systems, we are still a step lagging in giving them an application for educational purposes. This paper proposes a complete new idea of having a portal where they can store audio books aided with interactive system so that they can use them whenever needed.